HUBUNGAN KECERDASAN INTELEKTUAL DENGAN HASIL BELAJAR EKONOMI PADA SISWA KELAS XI SMA NEGERI 05 PONTIANAK - Niviea Pratiwi; Achmadi Achmadi; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstrack This study aims to find out the relationship of intellectual intelligence with economic learning outcomes in grade XI students of SMA Negeri 05 Pontianak. The research method used is descriptive method. The form of research is interelationship studies. The population in this study was all grade XI students consisting of 11 learning rombels, grade XI MIA 6 rombel and class XI Social 5 rombel. The sample of the study was 35 students in grade XI Sos 1. The results showed: 1) Intellectual intelligence in grade XI students of SMA Negeri 05 Pontianak amounted to 93.8, can be seen from the intellectual intelligence benchmark in students categorized as "Excellent". 2) The results of economic learning in grade XI students of SMA Negeri 05 Pontianak were obtained 91.28, can be seen in the existing benchmarks, then obtained economic learning results in students categorized as "Excellent". 3) There is a relationship of intellectual intelligence with economic learning results in grade XI students of SMA Negeri 05 Pontianak, the calculation result is rxy count = 0.426 while rxy table for n = 35 at the level of trust 95% is 0.334 (Arikunto, 2009:333). So from the conclusion there is a relationship of intellectual intelligence with the results of economic learning in grade XI students of SMA Negeri 05 Pontianak, the category of relationship "Medium" Keywords: Intellectual Intelligence, Economic Learning Outcomes